Productivity enhancement and modelling of a new double-slope solar still with rubber scrapers in low latitude areas - Al-Sulttani, Ali Omran Muhsin (2018)
Potable water is vital for our existence. Despite the fact that more than three-quarters of the earth is covered by water, only 0.014% of it is potable. Therefore, sustainable, safe, cheap, and environment-friendly techniques must be developed to produce potable water from salty water. Solar distillation is a promising method that is safe for the environment and uses only sustainable energy for its operation. The productivity of a solar still becomes a major challenge and therefore necessitates many modifications in design and operation to increase its amount. A solar still with high productivity can be achieved when the condensing cover slope is the same as the latitude angle of the solar still location. The main problem that occurs in the solar still is the fall down of water condensate from the glass cover due to gravity. In this study, a new double slope solar still hybrid with rubber scrapers (DSSSHS) and a double slope solar still (DSSS) were designed with a 3.0° slope condensing cover. The main objective of the study is to obtain the maximum yield of distilled water by using the new DSSSHS during daytime. The proposed design of the new solar still utilizes the advantage of using a condensing cover with a small slope angle to allow the entry of the maximum amount of solar radiation into the still. The disadvantages caused by the condensing cover with a small slope were overcome by using rubber scrapers. In this research, two (2) double slope solar stills one with rubber scrapers and the other without rubber scrapers were designed and fabricated. In the two solar stills, the condensing cover was placed at 3.0° which is equal to the latitude angle of the experiment location. Several experiments were conducted using the newly designed solar stills under different climatic conditions. The productivities of the two new solar stills were measured experimentally. For comparison, the saline water used and the distilled water produced from the DSSSHS were characterized. Experimental results obtained from the DSSSHS were used to construct the prediction models using the linear regression method and particle swarm optimization (PSO) algorithm with the aid of MATLAB software. The prediction models are the regression model, Particle Swarm Optimization Algorithm-Hourly Yield of Solar Still (PSO-HYSS) model, and extended PSO-HYSS model. In terms of the orientation of the still, there is an increase in daily productivity which varies from 12.3% to 13.2% when using east-west orientation compared with the north-south orientation. Moreover, the experimental results showed that the daily productivity of the DSSSHS (4.24 L/m2.day) is higher than that of DSSS (2.6 L/m2.day) under the same design, environmental and operational conditions. This result signifies that the use of rubber scrapers had enhanced the productivity of the still by 63%. The results showed that the productivity of DSSSHS per unit solar radiation is directly proportional to the number of scraper movements per hour (NSM). The predicted yields of the three prediction models were compared with their corresponding experimental yields to evaluate their accuracy. The results showed that the extended PSO-HYSS model is the most accurate, followed by the PSO-HYSS model and then the regression model.